The Vulva / Vaginal Diseases in Daily Practice - Gamze Çağlar; Elif Didem Özdemir; Sevim Cengiz; Handan Doğan (Medical Network, 2011)
OBJECTIVE: To emphasize the neglected vulva/vaginal lesions and symptoms commonly encountered in daily practice. STUDY DESIGN: The data of 98 patients with vulva or vaginal biopsies were collected retrospectively. The histopathological diagnosis of 82(83.67%) vulvar and 16(16.32%) vaginal biopsy cases were evaluated. RESULTS: The most common symptom was mass in 67% and 62% of cases in vulvar and vaginal region, respectively. Among the vulvar lesions the most frequent histopathological diagnoses were condyloma acuminatum (20.73%), hyperkeratotic papilloma (14.63%), non-spesific inflammatory changes (12.19%), fibroepithelial polyp (9.75%) and bartholin cyst (8.53%). On the other hand, the histopatological evaluation of the vaginal lesions revealed vaginal stromal polyp (25%) and gartner cyst (25%) as the most frequent lesions. CONCLUSIONS: The results of the study document lesions commonly not well known or disregarded by gynecologists. The literature is inconclusive about vulvavaginal diseases. Expanded data will help the clinicians in making correct diagnoses and patient managament.